The Longest War : The Enduring Conflict Between America and Al-Qaeda - Bergen, Peter L., 1962- (London Simon & Schuster Ltd., 2011)
New York Times bestselling author Peter Bergen's definitive account of al Qaeda's evolution since 9/11 and the U.S. government's responses.
Include Map, Colour Illustration, Notes, Interviewees, Bibliography and Index
Keywords: Terrorism--Prevention -- United States -- Iraq -- War on Terrorism (2001-2009) -- Iraq War (2003-2011) -- Qaida (Organization) -- Al-Qaida